2009
DOI: 10.1089/met.2008.0099
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Pro12Ala in the Peroxisome Proliferator-Activated Receptor γ2 Gene in Iranian Diabetic and Obese Subjects

Abstract: Our results showed that the Pro12Ala polymorphism in the PPARgamma2 gene is associated with obesity in Iranian subjects and the presence of the Ala allele could predict higher BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
4
19
3
Order By: Relevance
“…Regarding the relationship between the PPARg2 gene Pro12Ala polymorphism and blood lipids, the conclusions were also controversial (Douglas et al, 2001;Hasstedt et al, 2001;Ereqat et al, 2009;Mirzaei et al, 2009). We found that Ala allele frequencies were significantly different between those with hypertension with elevated blood lipids (P = 0.040) and the control group.…”
Section: Discussionmentioning
confidence: 62%
“…Regarding the relationship between the PPARg2 gene Pro12Ala polymorphism and blood lipids, the conclusions were also controversial (Douglas et al, 2001;Hasstedt et al, 2001;Ereqat et al, 2009;Mirzaei et al, 2009). We found that Ala allele frequencies were significantly different between those with hypertension with elevated blood lipids (P = 0.040) and the control group.…”
Section: Discussionmentioning
confidence: 62%
“…Nine cohort studies [12,25,26,27,28,29,30,31,32], 7 population case-control studies [33,34,35,36,37,38,39], 31 cross-sectional studies [5,7,10,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67], and 9 interventional studies [8,68,69,70,71,72,73,74,75] were included in the meta-analysis of the association between PPARγ Pro12Ala polymorphism and obesity. The characteristics and results of the studies are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics and results of the studies are summarized in table 1. Seven population case-control studies [33,34,35,36,37,38,39], and 1 cross-sectional study [10] provided their data in 2 datasets. Each dataset was treated as a separate comparison in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although early findings were inconsistent, replication studies and meta-analyses confirmed modest but significant increase in type 2 diabetes risk associated with the Pro allele (12). However, the relationship of Pro12Ala variant with obesity, MetS and related traits is less defined (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Similarly, conflicting results were obtained regarding the association between met abolic phenotypes and another frequent variant, a silent mutation in exon 6 of the PPARG gene, 1431C>T (c.1431C>T, rs3856806) (13, 14, 16-18, 23, 24).…”
Section: Introductionmentioning
confidence: 99%